Prevalence and consequences of vitamin A deficiency in pregnant women in Pakistan and the role of strategic nutritional policies - Muhammad Haseeb; Javeria Latif; Muhammad Shahwaiz Lund; Hassan Iqbal Abbasi; Javed Iqbal (Discover Public Health)
Abstract The people in Pakistan, like in many less developed countries, experience significant Vitamin A deficiency (VAD). It is widespread among individuals with increased nutritional demands, including Pregnant Women. The prevalence of vitamin A deficiency in Pakistan is 30% in non-pregnant women and 27% in pregnant women. This categorizes it as a country with widespread subclinical VAD. Insufficient dietary intake and suboptimal dietary diversity, imprudent prenatal care, negligence and unfamiliarity, and numerous other socioeconomic factors are the main contributing factors to VAD. Night blindness (with 12.7% prevalence reported in Pakistani pregnant women), impaired iron metabolism, decreased immune response, gestational diabetes, low birth weight, and infant mortality are significant ramifications of VAD in gravid women. WHO, UNICEF, and USAID have initiated multidisciplinary nutritional interventions to alleviate VAD in countries with greater susceptibility, including Pakistan. Our findings underscore the need for integrated community-based nutrition education, enhanced antenatal supplementation programs, and strengthened government-private partnerships to address vitamin A deficiency. Meticulous prenatal care and awareness of Vitamin A’s significance in pregnant individuals is required locally. In tandem with multi-professional healthcare providers, the government must prioritize implementing viable strategies to ameliorate VAD.